Belize : Technical Assistance Report-Cybersecurity, Regulation, Supervision, and Resilience. (IMF Staff Country Reports; Country Report ;, 2020)
Cybersecurity risk is embedded in the CBB's supervisory framework, but additional enhancements are needed to formalize guidance and develop more intensive supervisory practices. Supervisory expectations on cybersecurity are presented in an informal guidance note, which should be formalized into regulation to ensure enforceability; and an IT/cybersecurity supervisory manual should be developed to promote effective and consistent practices. With its principle-based guidance note, the CBB highlights its priorities in strengthening the cybersecurity posture of Belizean financial institutions. The principles are an appropriate interpretation of international best practices on incident prevention, detection, response, and recovery measures, adapted to the cyber maturity of the Belizean financial institutions, and can be used as a foundation for the formalized guidelines. The manual could emphasize the review of cybersecurity strategies, policies, and responsibility specifications and should address obtaining assurance on the effectiveness of the financial institutions' processes for cyber risk identification, assessment, and mitigation.